Growth ability, antimicrobial activity and suceptibility to antimicrobials of two strains of Pediococcus pentosaceus, candidates to probiotic - García-Hernández, Yaneisy; Pérez-Sánchez, Tania; García-Curbelo, Yanelys; Sosa, Dailyn; Nicoli, Jacques R. (Cuban Journal of Agricultural Science, 2018)
The objective of this study was to evaluate growth capacity, antimicrobial activity and susceptibility to antimicrobials of two strains of Pediococcus pentosaceus (LB-12 and LB-25), which are candidates for probiotic. For this, four trials with randomized designs and three repetitions were performed. Strain growth in MRS medium at 37 ºC had a similar performance and after 6 h of cultivation, they reached the stationary phase. Their growth rates were approximately 0.5 h-1 and duplication times were 1.3 h. Both were able to grow and decrease the pH of a culture medium where fructans of Agave fourcroydes were used as an energy source, although their concentration decreased with respect to the MRS medium. In addition, strains inhibited the growth of the evaluated pathogenic bacteria, with superior antimicrobial action of LB-25 against Salmonella enterica subsp. Enterica serovar Typhimurium ATCC 14028 and Listeria monocytogenes ATCC 1531. Candidates for probiotic were sensitive to penicillin G, florfenicol, chloramphenicol, amoxicillin, clavulanic acid and doxycycline. In turn, they were resistant to trimethoprim-sulfamethoxazole, cephalexin, tetracycline, vancomycin, nalidixic acid, oxalinic acid, enrofloxacin and flumequine, streptomycin, kanamycin and gentamicin. It is concluded that P. pentosaceus LB-12 and LB-25, in vitro, have antimicrobial activity against pathogens, are susceptible to antimicrobials and have adequate growth ability in MRS medium and using fructans as energy source, which would allow their inclusion in probiotic and symbiotic formulations for animal production.Key words: lactic bacteria, additives, microbial growth